Konservasi Air Tanah Melalui Pembuatan Sumur Resapan Air Hujan Di Kelurahan Maradekaya Kota Makassar - Azis, Akhmad; Yusuf, Hamzah; Faisal, Zulviyah (Politeknik Negeri Ujung Pandang, 2016)
Objectives to be achieved from the program science and technology for the Community (IbM) This is a crisis of groundwater that occur in the District Maradekaya, Makassar City can be resolved as well as long term targets is to encourage the local government of Makassar for the decision on the obligation for the people of Makassar making infiltration wells in his yard. The method will be used in these activities in the form of counseling for people in RW 03 and RW 04 about the dangers of groundwater in case of crisis, the way of making infiltration wells as well as manufacture in 5 homes in every RW (RW 03 and RW 04). Thetest results of water after infiltration wells through which rainwater is the quality of well water for the better. It is characterized by a decrease in turbidity of 27,5 %, NaCl 11,5 %, Sodium 12,3% and Chloride 11,1%.